HUBUNGAN POLA ASUH IBU DENGAN PERKEMBANGAN PERSONAL SOSIAL PADA ANAK PRA SEKOLAH DI PAUD FATMA KENANGA, KOTA BENGKULU - Dewi Aprilia Ningsih (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
The purpose of this study is to determine the Relationship of Parenting Mother with Development of Personal Social on Children Pre-School in PAUD X Bengkulu City.This study used survey analytic approach with cross sectional design. Population in this study were all parent with age of 5-6 years in PAUD X Bengkulu City with the amount of 33 people. Collecting data in this study used primary data with spreaded questionnaire of Parenting mother who given to the parents to filled out appropriate with parenting everyday, while collecting data development of Personal Social on Children with observation directly used Stimulation formulir, detection and Early Intervention of growth and depelopment. Data analysis used univariate and bivariate.The result of this study showed: (1) from 33respondent there were 42,4% with democratic parenting; (2) from 33 respondent there were 92,2% with Personal Social on Children in normal category and (3) There is significant relationship between parenting Mother with Development of Personal Social on Children Pre-School in PAUD X Bengkulu City with closed category relationship. Keywords: Parenting, Development of Personal Social